THE PROCESS OF THE HARD DOMESTIC WASTES ON PLASM REACTOR - Tatybekov, A.T.; Bugubaeva, M.A. (Recent Contributions to Physics, 2008)
In this work the process the hard domestic waste on plasma reactor in two versions, oblique and straight feed of the plasma torch in hard domestic waste is researched and it learned temperature dependence of the pyrolise from the temporarily process.